Kinetic study of glycerol-lauric acid esterification using 12-tungstophosphoric acid as a catalyst - Yuwansri, La-ongthip (Frontiers in Engineering Innovation Research, 2026)
This study aims to investigate the kinetics of the esterification reaction between glycerol and lauric acid using 12-tungstophosphoric acid (TPA) as a catalyst. The experiments were conducted in a 250 mL four-neck round-bottom flask, equipped with a stirring system and heated via a silicone oil bath. The effects of reaction temperature (110-170 oC) and molar ratio of lauric acid to glycerol (1:1–1:4) on the conversion of lauric acid were examined. The conversion was calculated based on free fatty acid (FFA) values determined by titration. The results indicated that the optimal condition was achieved at a molar ratio of 1:3, temperature of 170 oC, catalyst loading of 1 wt% of lauric acid, and a reaction time of 60 min, yielding a maximum lauric acid conversion of 89.2%. Kinetic analysis revealed that the reaction follows second-order kinetics, with a rate constant (k) of 0.0236 L/mol·min at 170 oC. The reaction rate equation is expressed as Rate = 0.0236[LA]² and an activation energy (Ea) of 67.92 kJ/mol.